Comparative clinical-related outcomes of Chinese patent medicines for cardiac hypertrophy: A systematic review and network meta-analysis of randomized clinical trials - Tianqi Zhang; Tianqi Zhang; Haoyang Xu; Dong Zhen; Danni Fu; Ming Zhao; Chengxi Wei; Xue Bai; Xue Bai (Frontiers Media S.A., 2023)
Background: Persistent pathological cardiac hypertrophy has been associated with increased risk of heart failure and even sudden death. Multiple Chinese patent medicines (CPMs) have gained attention as alternative and complementary remedies due to their high efficiency and few side effects. However, the effects of CPM-related treatment regimens for cardiac hypertrophy had not been systematically evaluated.Aim: The objective of this study was to estimate and compare the effectiveness of different mechanisms of CPMs to improve clinical outcomes, including clinical efficacy and echocardiographic indices, in the treatment of cardiac hypertrophy patents.Methods: A network meta-analysis was conducted on CPM-related randomized controlled trials (RCTs) published between 2012 and 2022 involving cardiac hypertrophy patients from four foreign and four Chinese databases. The outcomes concerned efficacy and related indicators, including echocardiographic indices, cardiac biomarkers, and functional exercise capacity, which were evaluated as odds ratios, mean differences, and 95% credible intervals. Network plots, league tables, surface-under-the-cumulative ranking (SUCRA), and funnel plots were created for each outcome, and all analyses were conducted using Stata 16.0 software.Results: A total of 25 RCTs were evaluated; these involved 2395 patients in a network meta-analysis (NMA). The results from existing evidence indicate that blood-activating and stasis-removing Chinese patent medicine (BASR-CPM) + Western medicine (WM) showed a good improvement in clinical efficacy (OR = 8.27; 95%CI = 0.97, 70.73). A combined treatment regimen of CPM with a function of qi-replenishing, blood-activating and stasis-removing, and Western medicine was an effective treatment regimen for echocardiographic indices such as decreasing left ventricular end-systolic dimension (LVESD) (SMD = −2.35; 95%CI = −3.09, −1.62) and left ventricular mass index (LVMI) (SMD = −1.73; 95%CI = −2.92, −0.54). Furthermore, KWYR-CPM + WM and BASR-CPM also showed good improvement for echocardiographic indices of LVEDD (SMD = −1.84; 95%CI = −3.46, −0.22) and left ventricular ejection fraction (SMD = 1.90; 95%CI = −0.46, −3.35), respectively.Conclusion: The study showed that BASR-CPM + WM may be the potentially superior treatment regimen for improving clinical efficacy among cardiac hypertrophy patients. QR&BASR-CPM + WM might be the optimal treatment for decreasing LVESD and LVMI. However, due to potential risks from bias and limited RCTs, further studies with larger samples and high-quality RCTs are needed to support these findings.Systematic Review Registration: [https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=329589],identifier [CRD42022329589].